A Tracer Study of the Doctor of Education Graduates in a State University in the Philippines - Buenvinida, Lerma P.; Manaig, Karen A.; Rodriguez, Maria Teresa M.; Salandanan, Flora H.; Buama, Chester Alexis C.; Tamban, Victoria E. (Transactions on Engineering and Computing Sciences, 2023)
This descriptive study examined the relevance and effectiveness of the Doctor of Education program of Laguna State Polytechnic University, Los Banos, Laguna, Philippines; demographic profiles of respondents such as age, gender, civil status, position, school type and details of promotion; achievement in current job, evaluation of achievement of program goals, and achievement of program outcomes. Based on the results, the program has successfully achieved its goal of developing a workforce of leaders capable of playing a key role at the primary, secondary and tertiary levels. This is reflected in the promotion of graduates to higher management positions such as superintendents, principals, and other supervisory positions in public school districts. Graduates feel that their degree has given them the confidence to establish themselves as educational leaders, work well with stakeholders, improve their communication and leadership skills, are satisfied and constantly strive to advance professionally and advance to the next rank. Successful practices in the areas of educational administration, school administration and resource management, incentives and employer’s feedback should be documented.